Strategi Pengembangan Seni Rebana Desa Sumberarum Melalui Pelatihan Media Branding - Marisa Qonita; Fuad Hilmy; Siti Lailatul Khusna; Junita Apriliani; Rian Adnan Fauzi; Muhammad Najih Jazuli (Jurnal Pemberdayaan Masyarakat, 2024)
In the era of globalization and technological advancement like today, websites are one of the alternative ways to share information and promote various activities. However, the lack of understanding and utilization of websites by the Sumberarum community makes the use of websites less than optimal. Based on the results of the 2023 PPKO program above, Sumberarum Village is one of the villages that has potential in the field of religious arts, especially rebana, to be introduced in surrounding villages. One solution to this problem is to conduct branding training using a website. The method used in this activity is the PAR (Participatory Action Research) method which aims to learn in overcoming problems and fulfilling the practical needs of the community, as well as the production of knowledge, and the process of socio-religious change. The purpose of this training is that the Sumberarum community can manage the website and be able to brand rebana using the website. The conclusion of this community service activity is that the activity has been carried out well as evidenced by the achievement of the planned target, the team's ability to show their talents and the youth in managing branding media. With this development program, it is hoped that it can accommodate the potential of the residents and make Sumberarum Village a village based on religious culture.